2019
DOI: 10.1007/s00430-019-00610-z
|View full text |Cite
|
Sign up to set email alerts
|

Adverse immunological imprinting by cytomegalovirus sensitizing for allergic airway disease

Abstract: Cytomegalovirus (CMV) infection has a profound impact on the host's immune system. Immunological imprinting by CMV is not restricted to immunity against CMV itself, but can affect immunity against other viral or non-viral infectious agents and also immunopathological responses. One category is heterologous immunity based on molecular mimicry, where antigen recognition receptors specific for a CMV antigen with broad avidity distribution also bind with some avidity to unrelated antigens and exert effector functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…CMV is known to challenge the immune system, altering the immune response to other pathogens (85). Both EBV and CMV cause a redistribution in B-cell subsets (86)(87)(88).…”
Section: Discussionmentioning
confidence: 99%
“…CMV is known to challenge the immune system, altering the immune response to other pathogens (85). Both EBV and CMV cause a redistribution in B-cell subsets (86)(87)(88).…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, the virus reaches the mucosal surfaces of the upper and lower airways [64][65][66]. As we have shown in the mouse model, mCMV airway infection can promote allergic airway disease by activating migratory dendritic cells [67,68], and airway challenge infection of latently infected mice can recruit effector-memory CD8 T cells from the vascular compartment to the alveolar epithelium [69]. It is, thus, more than likely that CMVs meet MC at respiratory tract surfaces and that MC do not remain uninvolved.…”
Section: Cytomegalovirus Pathogenesis and Its Relation To Airway Infe...mentioning
confidence: 92%
“…Haiyu et al found that influenza virus (IAV) more powerfully induced the expression of IL-25 in vitro, and IL-25 positively correlated with the load of IAV (103). A respiratory allergic reaction caused by cytomegalovirus (CMV) is also associated with IL-25 secretion (104). IL-25 treatment exacerbates mouse intestinal West Nile virus (WNV) infection (105).…”
Section: Other Virusesmentioning
confidence: 99%